Differences in winning techniques and time duration of fight between male and female judo competitors at the Universiade - 2007 - Kajmovic, H.; Radjo, I.; Mekic, A.; Kapo, S. (World Congress of Performance Analysis of Sport VIII, 2008)
This research was based on video analysis 297 fights for male and 222 fights for female competitors in all seven judo categories at the Universiade, Bankok - 2007. years. Judo fights were monitored trough five main variables. Comparasions were made trough Chi square test at the level of statistical importance (p<0,05) with contingency tables. The results of ÷2-test show that there are differences between applied groups of judo techniques and subgroups of judo techniques . Chi squere tests showed that is no statistically differences between technical points and penalties and time duration of fight. Winning techniques mostly used by male competitors were: KGU (7,9%), UMA (7,5%), SUK (7,5%), KTA (6,8%) etc. Winning techniques mostly used by female participants were: OUG (8,6%),YSG (4,5%), UMA (4,1%) etc. Researches analysis of the indicators of winning techniques, which competitors realize during the competitions represent good base for the applying researching results of training. Efficient action of judo fighter cannot be described as uncontrolled or unorganised, in the same manner as it is not possible that at a certain moment all these indicators are maximised at the same time. Monitoring and controlling of the efficiency of the relevant winning parameters in judo that are expressed by male and female could be directly applied into training process so that optimal choice of content and load for training could be assured.